La Vie et les œuvres de Philippe de Monte - Doorslaer, Georges van 1864-1940 (Brussels Lamertin Hayez, 1921)
Van Doorslaer, a Belgian musicologist, was president of the Cercle archéologique de Malines and a member of the Académie royale d'archéologie de Belgique. A physician by profession, he studied music as a vocation. He wrote valuable essays such as 'Kerry Bredemers, 1472-1522' (Antwerp, 1915), 'De Toonkunstenaars der familie Vredeman' (Antwerp, 1920), 'La Vie et les œuvres de Philippe de Monte' (Brussels, 1921), and 'Rinaldo del Mel' (Antwerp, 1922). He also edited eight volumes in the collected edition of works by Philippe de Monte.
Paper binding
Mémoire présenté à la Classe des beaux-arts dans la séance du 4 mai 1921
Keywords: Monte, Philippe de -- 1521-1603; 16th Century (1501-1600); 20th Century (1901-2000); Composer; Vocal music; Biography; Flanders (Belgium); Bohemia (Czech Republic); bewerkingen_16e eeuw; bezetting (voc.); oude muziek vroeger; Palestrina; Ph. de Monte; emoties; gamba; zangeres; Lassus, O. di_en Ph. de Monte; salaris; luit; luitduetten; Macque, J. de; Macque, J. de_ en Ph. de Monte; madrigaal; Marenzio, L; Monte, Philippe de_orgelmuziek; Monteverdi, C; Byrd, William; Cabezon, A. de; colorieren; Hoove, J. v.d.; klaveciniste_16e eeuw; Luyton, C; musica reservata; Paix, J; Viola, O. della; Woltz, J